Analysis of microsaccades during extended practice of a visual discrimination task in the macaque monkey. (19th January 2021) - Raffi, Milena; Meoni, Andrea; Piras, Alessandro
Highlights: Microsaccades indicate the locus of attention while executing a visual discrimination task. Microsaccade directions are linked to the peripheral attention. Oculomotor control of microsaccades is not influenced by experience. Learning does not influence the microsaccade generation. Abstract: The spatial location indicated by a visual cue can bias microsaccades directions towards or away from the cue. Aim of this work was to evaluate the microsaccades characteristics during the monkey's training, investigating the relationship between a shift of attention and practice. The monkey was trained to press a lever at a target onset, then an expanding optic flow stimulus appeared to the right of the target. After a variable time delay, a visual cue appeared within the optic flow stimulus and the monkey had to release the lever in a maximum reaction time (RT) of 700 ms. In the control task no visual cue appeared and the monkey had to attend a change in the target color. Data were recorded in 9 months. Results revealed that the RTs at the control task changed significantly across time. The microsaccades directions were significantly clustered toward the visual cue, suggesting that the animal developed an attentional bias toward the visual space where the cue appeared. The microsaccades amplitude differed significantly across time. The microsaccades peak velocity differed significantly both across time and within the time delays, indicating that the monkey made faster microsaccades when it expected the cue to appear. The microsaccades number was significantly higher in the control task with respect to discrimination. The lack of change in microsaccades rate, duration, number and direction across time indicates that the experience acquired during practicing the task did not influence microsaccades generation.